A genome‐wide phylogeny and the diversification of genus Liriomyza (Diptera: Agromyzidae) inferred from anchored phylogenomics. (15th September 2022) - Xuan, Jing‐Li; Scheffer, Sonja J.; Lonsdale, Owen; Cassel, Brian K.; Lewis, Matthew L.; Eiseman, Charles S.; Liu, Wan‐Xue; Wiegmann, Brian M.
Abstract: The genus Liriomyza Mik (Diptera: Agromyzidae) is a diverse and globally distributed group of acalyptrate flies. Phylogenetic relationships among Liriomyza species have remained incompletely investigated and have never been fully addressed using molecular data. Here, we reconstruct the phylogeny of the genus Liriomyza using various phylogenetic methods (maximum likelihood, Bayesian inference, and gene tree coalescence) on target‐capture‐based phylogenomic datasets (nucleotides and amino acids) obtained from anchored hybrid enrichment (AHE). We have recovered tree topologies that are nearly congruent across all data types and methods, and individual clade support is strong across all phylogenetic analyses. Moreover, defined morphological species groups and clades are well‐supported in our best estimates of the molecular phylogeny. Liriomyza violivora (Spencer) is a sister group to all remaining sampled Liriomyza species, and the well‐known polyphagous vegetable pests [ L. huidobrensis (Blanchard), L. langei Frick, L. bryoniae. (Kaltenbach), L. trifolii (Burgess), L. sativae Blanchard, and L. brassicae (Riley)]. belong to multiple clades that are not particularly closely related on the trees. Often, closely related Liriomyza species feed on distantly related host plants. We reject the hypothesis that cophylogenetic processes between Liriomyza species and their host plants drive diversification in this genus. Instead, Liriomyza exhibits a widespread pattern of major host shifts across plant taxa. Our new phylogenetic estimate for Liriomyza species provides considerable new information on the evolution of host‐use patterns in this genus. In addition, it provides a framework for further study of the morphology, ecology, and diversification of these important flies. Abstract : Phylogenetic relationships are reconstructed among the Liriomyza leafminers using phylogenomic analysis of nuclear gene loci obtained by anchored hybrid enrichment (AHE). Trees inferred using multiple data types and analysis methods are congruent and individual clade support confirms morphological species groups and relationships among them. Liriomyza violivora (Spencer) is placed sister to all sampled Liriomyza species, and the polyphagous vegetable pests [ L. huidobrensis (Blanchard), L. langei Frick, L. bryoniae (Kaltenbach), L. trifolii (Burgess), L. sativae Blanchard, and L. brassicae (Riley)] do notform a single clade on the phylogeny. Our findings demonstrate that closely related Liriomyza species feed on distantly related host plants and species diversification does not support a history of tightly associated cophylogenesis between Liriomyza species and their host plants.